2017
DOI: 10.1080/09638237.2017.1294732
|View full text |Cite
|
Sign up to set email alerts
|

Social and occupational factors associated with psychological wellbeing among occupational groups affected by disaster: a systematic review

Abstract: 1Social and occupational factors associated with psychological wellbeing among occupational groups affected by disaster: A systematic review ABSTRACT Background The psychological impact of experiencing disasters has been welldocumented; less attention has been paid to factors affecting the wellbeing of those exposed to disasters as part of occupational groups.Aims To conduct a systematic literature review identifying social and occupational factors affecting the wellbeing of disaster-exposed employees; to use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
53
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 56 publications
3
53
0
7
Order By: Relevance
“…Firstly, it appeared that training, and consequential feelings of preparedness, were protective of mental health. This is unsurprising as perceived adequacy of training and feelings of preparedness have been associated with more positive psychological wellbeing in humanitarian relief workers, disaster responders and trauma-exposed employees in general 6,7,8 . In particular, the increased confidence in ability to do one's job as a result of specialised training appeared to be protective.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, it appeared that training, and consequential feelings of preparedness, were protective of mental health. This is unsurprising as perceived adequacy of training and feelings of preparedness have been associated with more positive psychological wellbeing in humanitarian relief workers, disaster responders and trauma-exposed employees in general 6,7,8 . In particular, the increased confidence in ability to do one's job as a result of specialised training appeared to be protective.…”
Section: Discussionmentioning
confidence: 99%
“…Factors only described in one paper were excluded as it was unclear whether there was any support for these factors; any factors described in two or more papers were included as we felt that given the small number of papers, this was sufficientor at least worth exploring. Previous reviews have used a similar method of accepting any predictive factor mentioned by at least two studies 6,7,8 . If disagreements between studies were found then both viewpoints were discussed.…”
Section: Data Extraction Quality Appraisal and Data Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review of occupational groups affected by disaster (Brooks et al, 2017) suggested that pre-disaster experiences, job satisfaction, traumatic exposure, perception of safety, harm to self/close others, social support, and post-disaster impact on life were important to all workers. In terms of public servants, government staff who were in close proximity to disasters including terror attacks showed greater prevalence of low mental health, post-traumatic stress disorder symptoms, depression, and alcohol abuse (Grieger et al, 2004(Grieger et al, , 2005Hansen et al, 2013;Jordan et al, 2004) than those who were not.…”
mentioning
confidence: 99%
“…In Japan, public servants are often criticised by the public in everyday circumstances because many Japanese people believe that public servants are stable in various aspects, such as employment, salary, and social security. In terms of social factors in times of disaster, workers received a lack of positive acknowledgement from others, which was associated with low mental health (Brooks et al, 2017). Therefore, Japanese public servants in disaster areas would be more susceptible to low mental health than would be those with other occupations, because of proximity to the disaster and a lack of social acknowledgement.…”
mentioning
confidence: 99%